Síntese coloidal de nanocristais magnéticos com superfície macromolecular - Gonçalves, Ricardo Henrique (Universidade Federal de São Carlos, 2009)
This dissertation describes the development of a synthetic route to obtain colloidal magnetic nanocrystals in solvent of high molar weight and different polarities. Magnetite Nanocrystals ware synthesized by thermal decomposition method using organometallic. With this method was possible to control the size of nanoparticle, obtain high crystallinity and control solubility in several organic solvents. The results showed that the nanocrystals solubility synthesized by this method is governed by polarity of macromolecular solvents. Hydrophobic macromolecule became hydrophobic magnetic nanocrystals. On the other hand, hydrophilic macromolecule result hydrophilic magnetic nanocrystals, like this amphiphilic macromolecule solvent transfer these properties to nanocrystals, turning them into amphiphilic. This solubility behavior was clarified by infrared spectroscopy analysis, indicating the existence of anchored macromolecules on the nanocrystals surface. Besides the crystallographic phase obtained, was also possible obtain superparamagnetic material and high saturation magnetization, revealing so that these colloidal magnetic nanocrystals have potential for biological application.
Keywords: Química coloidal; Magnetita; Superparamagnético; CIENCIAS EXATAS E DA TERRA::QUIMICA